Corrosion Behavior of an Equiatomic CoCrFeMnNi High-Entropy Alloy- a Comparison Between Selective Laser Melting and Cast - Peng, Haoping; Lin, Zehuan; Li, Ruidi; Niu, Pengda; Zhang, Zhijian (Frontiers in Materials, 2020)
The corrosion behaviors of equiatomic CoCrFeMnNi high-entropy alloys (HEAs) were comparatively investigated between selective laser melting (SLM) and casting. The casted sample shows better corrosion resistance in 3.5 wt. % NaCl solution than the SLM printed samples due to the higher density of dislocations, pores, and cracks in SLM samples, which significantly reduces their corrosion resistance. Furthermore, it is found that the corrosion resistance is different between the planes parallel and perpendicular to the building direction because of the differences in grain orientation, grain size, and surface morphology. Electrochemical anode dissolution rates of the SLM printed CoCrFeMnNi HEAs on their planes parallel and perpendicular to the building direction are calculated and the results show that the pores and cracks dominate the corrosion resistance rather than the grain boundary and the grain orientation.